SEMIOTIC ANALYSIS OF THE ROLE OF “NEWSPEAK” AS A SYMBOL OF MIND CONTROL IN THE NOVEL “1984” BY GEORGE ORWELL - Cindy Rima Amanda; Hendra Hendra; Aa Qonaatun (CV. Bunda Ratu, 2026)
This study analyzes Newspeak as a symbol of mind control in George Orwell’s 1984, highlighting how totalitarian regimes manipulate language to restrict thought and control ideology. Using a qualitative content analysis based on Klaus Krippendorff’s method, ten key Newspeak vocabularies were examined semiotically through Peirce’s triadic model and interpreted via Wellek and Warren’s sociology of literature. Findings reveal that Newspeak systematically simplifies language and eliminates alternative meanings to align consciousness with Party doctrine, serving as a subtle yet powerful tool for controlling thought, speech, and emotion. This study underscores Orwell’s warning that controlling language equates to controlling the human mind.